Beam, diffuse and global solar irradiance estimation with satellite imagery. (15th November 2015) - Alonso-Montesinos, J.; Batlles, F.J.; Bosch, J.L.
Highlights: A methodology was developed for estimating beam, diffuse and global radiation. The three solar radiation components are estimated under all sky conditions. Remote sensing techniques were applied to satellite images for estimating radiation. Results are shown for cloudless, partially-cloudy and overcast skies for 2010–2014. In general, estimations for cloudless skies presents better results than cloudy days. Abstract: The increase in applications related to solar energy is making it necessary to study those factors related to improving system efficiency and final production. Electricity generation in solar power systems, such as concentrated solar power and photovoltaic plants is governed by meteorological conditions. The presence of attenuating atmospheric factors determines the sun's intermittent character, causing electricity generation instability. Consequently, these fluctuations cause problems when integration the generated electricity into the public electricity grid, resulting in variability and unpredictability in the electricity market. Therefore, choosing a climatologically optimal place to install solar plants is fundamental for optimizing the final electricity generation. Besides this, constantly-updated solar information can contribute to take transcendental decisions and, consequently, in the performance of solar applications. Accordingly, a real-time solar radiation estimation is presented using satellite images, where beam, diffuse and global components have been evaluated in real time for all sky conditions.